2013
DOI: 10.12968/bjcn.2013.18.sup6.s34
|View full text |Cite
|
Sign up to set email alerts
|

A fresh way to treat venous leg ulcers with measured compression

Abstract: Information about health is gained from various sources but little is known about the health information-seeking behaviours of older people and what factors affect this. This pilot study aimed to explore older people's experiences and views on their health information-seeking behaviours and to gain a better understanding of these. A qualitative study with nine older people was undertaken, using diaries and semi-structured interviews to gather data. Three key themes emerged relating to why they sought informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…Second, there was not the expected magnitude of increase in the use of Internet and social media, with the majority of respondents still relying primarily on traditional media information sources. This finding is particularly relevant given the realities of our aging population and their increasing needs for health information [ 46 ]. This pattern signals that the growing emphasis on providing official public health risk communication and information through Internet and social media sources, while important, should not replace the use of more traditional information channels.…”
Section: Discussionmentioning
confidence: 99%
“…Second, there was not the expected magnitude of increase in the use of Internet and social media, with the majority of respondents still relying primarily on traditional media information sources. This finding is particularly relevant given the realities of our aging population and their increasing needs for health information [ 46 ]. This pattern signals that the growing emphasis on providing official public health risk communication and information through Internet and social media sources, while important, should not replace the use of more traditional information channels.…”
Section: Discussionmentioning
confidence: 99%
“…The device was shown to be successful in managing oedema, healing complex ulcers, and in preventing ulcer reoccurrence. 29 Bianchi et al 28 described the use of the JuxtaCURES device in three patients with venous ulceration, reporting improvements in quality of life, pain, well-being and cost effectiveness. Others have described improvements in pain and depression, improved skin integrity, and enhanced self-care when patients were changed to an adjustable compression wrap system from traditional compression bandaging [29][30][31][32] although details of how these outcomes were measured are not clear.…”
Section: Adjustable Compression Wrap Devices In Venous Ulcer Managementmentioning
confidence: 99%
“…38 Several papers and posters suggested that self-care adjustable compression wrap devices provide cost savings associated with reduced use of bandaging materials, time saved due to quicker and easier application of the devices, application by the person or their carer, and fewer nurse visits or appointments for bandaging. 18,28,34,35 Further economic advantages are also identified as the adjustable compression wrap devices can be washed, and reused over a period of 6 months, providing a cheaper option than repeated bandaging.…”
Section: Economic Implications Of Using Adjustable Compression Wrap Dmentioning
confidence: 99%
“…38 Several papers and posters suggested that self-care adjustable compression wrap devices provide cost savings associated with reduced use of bandaging materials, time saved due to quicker and easier application of the devices, application by the person or their carer, and fewer nurse visits or appointments for bandaging. 18,28,34,35 Further economic advantages are also identified as the adjustable compression wrap devices can be washed, and reused over a period of 6 months, providing a cheaper option than repeated bandaging. 22,28…”
Section: Economic Implications Of Using Adjustable Compression Wrap Dmentioning
confidence: 99%
“…18,28,34,35 Further economic advantages are also identified as the adjustable compression wrap devices can be washed, and reused over a period of 6 months, providing a cheaper option than repeated bandaging. 22,28…”
Section: Economic Implications Of Using Adjustable Compression Wrap Dmentioning
confidence: 99%